“Slow walk” mimetic tensile loading maintains human meniscus tissue resident progenitor cells homeostasis in photocrosslinked gelatin hydrogel - Jing Sun; Yau Tsz Chan; Ki Wai Kevin Ho; Li Zhang; Liming Bian; Rocky S. Tuan; Yangzi Jiang (Bioactive Materials, 2023)
Meniscus, the cushion in knee joint, is a load-bearing tissue that transfers mechanical forces to extracellular matrix (ECM) and tissue resident cells. The mechanoresponse of human tissue resident stem/progenitor cells in meniscus (hMeSPCs) is significant to tissue homeostasis and regeneration but is not well understood. This study reports that a mild cyclic tensile loading regimen of ∼1800 loads/day on hMeSPCs seeded in 3-dimensional (3D) photocrosslinked gelatin methacryloyl (GelMA) hydrogel is critical in maintaining cellular homeostasis. Experimentally, a “slow walk” biomimetic cyclic loading regimen (10% tensile strain, 0.5 Hz, 1 h/day, up to 15 days) is applied to hMeSPCs encapsulated in GelMA hydrogel with a magnetic force-controlled loading actuator. The loading significantly increases cell differentiation and fibrocartilage-like ECM deposition without affecting cell viability. Transcriptomic analysis reveals 332 mechanoresponsive genes, clustered into cell senescence, mechanical sensitivity, and ECM dynamics, associated with interleukins, integrins, and collagens/matrix metalloproteinase pathways. The cell-GelMA constructs show active ECM remodeling, traced using a green fluorescence tagged (GFT)-GelMA hydrogel. Loading enhances nascent pericellular matrix production by the encapsulated hMeSPCs, which gradually compensates for the hydrogel loss in the cultures. These findings demonstrate the strong tissue-forming ability of hMeSPCs, and the importance of mechanical factors in maintaining meniscus homeostasis.